Theory and Engineering of Complex Systems and Dependability: Proceedings of the Tenth International Conference on Dependability and Complex Systems DepCoS-RELCOMEX, June 29 – July 3 2015, Brunów, Poland - Zamojski, W (Springer, 2016)
Building upon a long tradition of scientifi c conferences dealing with problems of reliability in technical systems, in 2006 Department of Computer Engineering at Wrocław University of Technology established DepCoS-RELCOMEX series of events in order to promote a comprehensive approach to evaluation of system performability which is now commonly called dependability. Contemporary complex systems integrate variety of technical, information, soft ware and human (users, administrators and management) resources. Their complexity comes not only from involved technical and organizational structures but mainly from complexity of information processes that must be implemented in specific operational environment (data processing, monitoring, management, etc.). In such a case traditional methods of reliability evaluation focused mainly on technical levels are insufficient and more innovative, multidisciplinary methods of dependability analysis must be applied. Selection of submissions for these proceedings exemplify diversity of topics that must be included in such analyses: tools, methodologies and standards for modelling, design and simulation of the systems, security and confidentiality in information processing, specific issues of heterogeneous, today often wireless, computer networks, or management of transportation networks. In addition, this edition of the conference hosted the 5th CrISS-DESSERT Workshop devoted to the problems of security and safety in critical information systems.